2016
DOI: 10.1002/jbmr.2818
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Atypical Femur Fractures in Cancer Patients: The MD Anderson Cancer Center Experience

Abstract: Atypical femoral fractures (AFFs) are rare adverse events attributed to bisphosphonate (BP) use. Few cases of AFF in cancer have been described; the aim of this study is to identify the incidence and risk factors for AFF in a large cancer center. This retrospective study was conducted at the MD Anderson Cancer Center. The incidence rate of AFF among BP users was calculated from January 1, 2004 through December 31, 2013. The control group (n = 51) included 2 or 3 patients on BPs matched for age (≤1 year) and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 49 publications
2
19
1
Order By: Relevance
“…AFFs have long been regarded as a new type of osteoporotic fractures. However, emerging sporadic evidence indicated that AFFs also occurred in patients receiving higher doses of BPs with more frequent intravenous injections (e.g., at a monthly dose of 4 mg zoledronate) for skeletal malignancies, such as bone metastasis and myeloma, supporting the long-standing opinion that severely decreased bone turnover due to either chronic or higher-dose BP exposure might be the underlying mechanism of AFFs [19] , [21] , [22] . A retrospective study by Puhaindran et al [21] indentified four patients with AFFs in 327 patients receiving at least 24 doses of intravenous BPs for cancer therapy.…”
Section: Affs In Patients Receiving Cancer-dose Bpsmentioning
confidence: 96%
See 1 more Smart Citation
“…AFFs have long been regarded as a new type of osteoporotic fractures. However, emerging sporadic evidence indicated that AFFs also occurred in patients receiving higher doses of BPs with more frequent intravenous injections (e.g., at a monthly dose of 4 mg zoledronate) for skeletal malignancies, such as bone metastasis and myeloma, supporting the long-standing opinion that severely decreased bone turnover due to either chronic or higher-dose BP exposure might be the underlying mechanism of AFFs [19] , [21] , [22] . A retrospective study by Puhaindran et al [21] indentified four patients with AFFs in 327 patients receiving at least 24 doses of intravenous BPs for cancer therapy.…”
Section: Affs In Patients Receiving Cancer-dose Bpsmentioning
confidence: 96%
“…However, it is still unknown whether this association can be attributed to the pathologically specific effect of alendronate on bone or can simply be a result of variation in the prescription rate of different types of BPs. Regardless of these epidemiological differences, all BPs used for treating OP are required to be prescribed with caution as these are associated with an increased risk for AFF, according to the Food and Drug Administration as well as the European Union [19] .…”
Section: Epidemiology Of Affs Associated With Bpsmentioning
confidence: 99%
“…Although both patients received anti-resorptives at much greater doses than those of osteoporosis patients, the two patients may have had osteoporosis before starting anti-resorptive therapy. More recently a larger review [10] of cancer patients on bisphosphonate therapy concluded that such patients were at higher risk for AFF than cancer patients not on bisphosphonates. However, from this review and earlier reports of AFF in patients not on bisphosphonates [9], it is not possible to know if such some of these patients had osteoporosis.…”
Section: Pathogenesis Of Atypical Femoral Fracturesmentioning
confidence: 99%
“…AFFs are categorized as incomplete or complete fractures and can often progress from incomplete to complete . The incidence of AFFs in cancer patients is 0.05 per 100 000 cases per year, with an odds ratio of 300 (patients administered with BRIs vs patients not administered BRIs) . The incidence of AFF increases when BRIs are administered for longer periods …”
Section: Introductionmentioning
confidence: 99%